Customized fetal growth standard compared with the INTERGROWTH‐21st century standard at predicting small‐for‐gestational‐age neonates. (16th July 2018) - Odibo, Anthony O.; Nwabuobi, Chinedu; Odibo, Linda; Leavitt, Karla; Obican, Sarah; Tuuli, Methodius G.
Abstract: Introduction: The INTERGROWTH‐21st project (IG‐21) was recently performed aiming to provide a universal benchmark for comparing fetal growth across different ethnicities. Our aim was to compare the IG‐21 with a customized standard for predicting pregnancies at risk for neonatal small‐for‐gestational age (SGA) and adverse outcomes. Material and methods: This was a prospective cohort study including singleton pregnancies presenting for fetal growth assessment between 26 and 36 weeks of gestation. Fetal growth restriction was defined as estimated fetal weight <10th centile for gestational age using IG‐21 and a customized standard. Neonatal SGA was defined as birthweight <10th centile for gestational age by the Alexander chart. Primary outcome was the prediction of neonatal SGA. Secondary outcomes included a composite of adverse neonatal outcomes. The discriminatory ability of each growth standard was compared using area under receiver operating characteristic curves (AUC). Results: Of 1054 pregnancies meeting the inclusion criteria, the incidence of neonatal SGA was 139 (13.2%), and a composite adverse neonatal outcome occurred in 300 (28.4%). The sensitivity of the customized standard (38.8%) was higher than that of IG‐21 (24.5%) for predicting neonatal SGA, with AUC (95% CI) of 0.67 (0.63‐0.71) for customized vs 0.62 (0.58‐0.65) for IG‐21; P = .003. Both standards were comparable in predicting the composite adverse neonatal outcomes: AUC (95% CI) 0.52 (0.50‐0.55) for customized vs 0.51 (0.50‐0.53) for IG‐21; P = 0.25. Conclusions: Both growth standards had modest performance in detecting neonatal SGA and were poor at predicting short‐term adverse neonatal outcome.